A tetraphenylethene-based polymer array discriminates nitroarenes - Huang, Wei; Bender, Markus; Seehafer, Kai; Wacker, Irene; Schröder, Rasmus R.; Bunz, Uwe H. F. (Macromolecules, 2018)
Four tetraphenylethene (TPE)-based aryleneethynylene-type polymers (TPEPs) are reported in this work. All of them show aggregate-induced emission (AIE). Their optical properties have been investigated. The TPEPs are tested as a sensor array for 14 different nitroaromatic analytes and display fingerprint fluorescence quenching responses. The TPEPs demonstrate good sensitivity and discriminatory power in detecting explosives. The quenching efficiencies are dependent on the spectral overlap areas (absorbance of the analyte and the emission of the fluorescent polymer) and on the LUMO level of the analytes. The specific quenching responses are recorded and visualized after processing the data by linear discriminant analysis (LDA). Fourteen nitroarenes are discriminated by the four-element sensor array. Even five pairs of regioisomeric nitroarenes with similar physical and chemical properties were easily discriminated.
Gesehen am 10.10.2019